EXPLORING THE WORLD OF WORDS: SPOKEN LANGUAGE ACQUISITION IN EARLY CHILDHOOD - Cahyani, Yunita Lintang; Desmi Ayu Sintia; Nurul Lailatul Qodriyati; Nargis (Media Inovasi Pendidikan dan Publikasi, 2024)
This study looks at word acquisition and how phonology is developed in children aged 1 year 8 months. Using qualitative descriptive methodologies and observation devices on youngsters via direct observation. The results of the existing data suggest that a child aged 1 year 8 months generates 34 words, with the phonology or sounds produced remaining distant but understood. Children can now discuss their daily requirements. Aside from that, environmental and family factors influence children's cognitive ability in word acquisition. Children's language development is also influenced by their interactions with their parents.